Repeated exercise in heat and exertional alterations to thermoregulation (REHEAT) - Anderson, C. A. J. (Queensland University of Technology, 2020)
This thesis is an investigation into the effects of repeated bouts of exercise and rest on core temperature responses between men and women, following current Australian Army work guidelines. The findings of this thesis suggest that the current guidelines appropriately protect both men and women working in the heat and may inform Australian Army decision making regarding appropriate durations for up to four repeated bouts of work and rest when working in extreme heat.